Strip-planting Rhizoma Peanut into Grazing Systems - Jose C. B. Dubeux; Lynn E. Sollenberger; Joao Vendramini; Marcelo O. Wallau; Ann R. Soffes Blount; Liza Garcia-Jimenez; Erick Santos; David Jaramillo (EDIS)
Nitrogen (N) is one of the major off-farm inputs in livestock systems, either in the form of N fertilizer or purchased feed. Fortunately, you can reduce those expenses by growing your own nitrogen using forage legumes. Rhizoma perennial peanut (RPP) is a legume adapted to the Florida environment that grows well in mixtures with bahiagrass. This 4-page fact sheet discusses varieties, establishment, weed management, grazing management, and the cost-share program. Written by Jose Dubeux, Lynn Sollenberger, Joao Vendramini, Marcelo Wallau, Ann Blount, Liza Garcia-Jimenez, Erick Santos, and David Jaramillo, and published by the UF/IFAS Agronomy Department, July 2018. http://edis.ifas.ufl.edu/ag421